EXPOSURE AND METABOLIC ACTIVATION BIOMARKERS OF CARCINOGENIC TOBACCO-SPECIFIC NITROSAMINES - Hecht, Stephen S. (Acc Chem Res, 2015)
Lung cancer is the leading cause of cancer death in the world, and cigarette smoking is its main cause. Oral cavity cancer is another debilitating and often fatal cancer closely linked to tobacco product use. While great strides have been made in decreasing tobacco use in the United States and some other countries, there are still an estimated 1 billion men and 250 million women in the world who are cigarette smokers and there are hundreds of millions of smokeless tobacco users, all at risk for cancer. Worldwide, lung cancer kills about 3 people per minute. This account focuses on metabolites and biomarkers of two powerful tobacco-specific nitrosamine carcinogens – 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N′-nitrosonornicotine (NNN) - considered to be among the main causes of lung cancer and oral cavity cancer in people who use tobacco products. Three properties of NNK and NNN are critical for successful biomarker studies: they are present in all tobacco products, they are tobacco-specific and are not found in any other product, and they are strong carcinogens. NNK and NNN are converted in humans to urinary metabolites that can be quantified by mass spectrometry as biomarkers of exposure to these carcinogens. They are also metabolized to diazonium ions and related electrophiles that react with DNA to form addition products that can be detected and quantified by mass spectrometry. These urinary metabolites and DNA addition products can serve as biomarkers of exposure and metabolic activation, respectively. The biomarkers of exposure, in particular the urinary NNK metabolites NNAL and its glucuronides, have been extensively applied to document tobacco-specific lung carcinogen uptake in smokers and non-smokers exposed to secondhand tobacco smoke. Highly sensitive mass spectrometric methods have been developed for quantitative analysis of these NNK metabolites as well as metabolites of NNN in human urine, blood, and toenails. Urinary and serum NNAL have been related to lung cancer risk, and urinary NNN to esophageal cancer risk, in prospective epidemiology studies. These results are consistent with carcinogenicity studies of NNK, NNAL and NNN in rats, which show that NNK and NNAL induce mainly lung tumors, while NNN causes tumors of the esophagus and oral cavity. Biomarkers of metabolic activation of NNK and NNN applied in human studies include the metabolism of deuterium labelled substrates to distinguish NNK and NNN metabolism from that of nicotine, and the determination of DNA and hemoglobin adducts in tissues, blood, and oral cells from people exposed to tobacco products. As these methods are continually improved in parallel with the ever increasing sensitivity and selectivity of mass spectrometers, development of a comprehensive biomarker panel for identifying tobacco users at high risk for cancer appears to be a realistic goal. Targeting high risk individuals for smoking cessation and cancer surveillance can potentially decrease the risk of developing fatal cancers.